Strengthening Teacher Professional Development through Teacher Working Groups: Insights from Educational Administration and Institutional Ethics - Djohar Djohar; Dety Yunita Sulanjari; Asdar Muhammad Nur (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
The Teacher Working Group (Kelompok Kerja Guru/KKG) plays a strategic role in supporting Sustainable Professional Development (Pengembangan Keprofesian Berkelanjutan/PKB) for elementary school teachers. However, previous studies have predominantly examined KKG from pedagogical perspectives, while limited attention has been given to its administrative governance and institutional ethics dimensions. This study aims to analyze the role of KKG in enhancing teacher professionalism in Gowa Regency through the perspectives of educational administration and institutional ethics. A qualitative case study approach was employed. Data were collected through in-depth interviews with KKG administrators, elementary school teachers, and school supervisors, supported by observations and document analysis. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. The findings reveal that KKG functions as a collaborative learning community that facilitates the sharing of teaching practices, pedagogical reflection, and professional competence development. Nevertheless, its effectiveness is constrained by weak strategic planning, limited resource and logistics management, inadequate coordination with educational authorities, and insufficient internalization of organizational ethics. Furthermore, teacher participation is often driven by administrative obligations rather than professional commitment, reducing the transformative potential of KKG activities. The study concludes that the success of teacher professional development through KKG depends not only on program implementation but also on the quality of institutional governance encompassing administrative, managerial, and ethical dimensions. Strengthening institutional capacity, participatory leadership, and sustainable policy support is therefore essential to optimize the role of KKG in improving the quality of elementary education.